QUADRIPAERESIS - A RARE CASE OF EPITHELOID HAEMANGIOENDOTHELIOMA. - Hegde, Deepak; Shetty, Vikram; Shetty, J. P.; B., Sandeep Kini (Journal of Health and Allied Sciences NU, 2012)
A 62 yr old male presented with complaints of neck pain associated with weakness of both upper and lower limbs for 2 months.Weakness began with upper limb progressing to involve the lower limbs.X-ray cervical spine showed C7 vertebral collapse with decreased joint spaces.MRI scan showed compression collapse of C7 vertebral body, thecal sac narrowing & cord changes at this level.C7 corpectomy and biopsy with anterior fusion with bone graft and instrumentation was performed revealing mass around C7 vertebra.Histology revealed fragments of cartilage, bone, & vascular tumorcomposed of well formed vessels lined by cuboidal to hobnail endothelium. Focal areas showed lymphocytic infiltration and occasional benign giant cells suggestive of haemangioendothelioma. The purpose is to present a rare tumour occurring at an unusual site presenting as cervical myelopathy.
Keywords: Quadriparesis; Haemangioendothelioma